Low-cost 3D nanocomposite solar cells obtained by electrodeposition of CuInSe2 - Valdes, Matias Hernan (2007)
Thin CuInSe2 films have been prepared by electrodeposition from a single bath aqueous solution on both dense and nanoporous TiO2. The films are deposited potentiostatically using a N2-purged electrolyte at different potentials. Various deposition times and solution compositions have been employed. The effect of annealing in air and in argon at different temperatures and times is also investigated. Thin films and nanocomposites of TiO2 and CuInSe2 have been studied with electron microscopy, X-ray diffraction, Raman spectroscopy, and optical absorption spectroscopy. After a thermal anneal in argon at 350 °C for 30 min excellent CuInSe2 is obtained. In particular the nominal crystal structure and the bandgap of 1.0 eV are found. Although pinholes are present occasionally, good samples with diode curves showing a rectification ratio of 24 at ±1 V are obtained. Upon irradiation with simulated solar light of 1000 W m−2 a clear photoconductivity response is observed. Furthermore, also some photovoltaic energy conversion is found in TiO2|CuInSe2 nanocomposites.